POTENTIAL INCOMPATIBILITIES IN PRIMARY CARE: PILOT STUDY - Nikolić, Božana (Medicinski časopis, 2024)
Introduction. Drug incompatibilities can compromise the safety and effectiveness of parenteral therapy. The aim of this study was to identify combinations of parenteral drugs that are prescribed in primary care and to analyze their potential for incompatibilities. Methods. A pilot cross-sectional study was conducted at the Health Center “Novi Sad”. Data on patients and drugs were collected from electronic health records. The potential for incompatibilities was analyzed at the level of drug pairs and in accordance with data in three literature sources. Results. In total, 196 drug pairs were identified: 56 (28.6%) were compatible, 16 (8.2%) were incompatible and compatibility was unknown for 124 (63.3%) pairs. Among incompatible pairs, 87.5% (14/16) were prescribed for intravenous administration. Pantoprazole was most often included in potential incompatibilities. Among pairs of unknown compatibility, 80.6% (100/124) were prescribed for intramuscular administration and mainly included dexamethasone, diclofenac, hydroxocobalamin and diazepam. Conclusion. Taking into account the frequency and risks of potential incompatibilities, proposing guidelines to their avoiding would be useful.